Disability-adjusted life years lost due to diabetes in France, Italy, Germany, Spain, and the United Kingdom: a burden of illness study - Darbà J; Kaskens L; Detournay B; Kern W; Nicolucci A; Orozco-Beltrán D; Ramírez de Arellano A (Dove Medical Press, 2015)
Josep Darbà,1 Lisette Kaskens,2 Bruno Detournay,3 Werner Kern,4 Antonio Nicolucci,5 Domingo Orozco-Beltrán,6 Antonio Ramírez de Arellano71Department of Economics, University of Barcelona, Barcelona, Spain; 2Department of Health Economics, BCN Health Economics and Outcomes Research SL, Barcelona, Spain; 3Department of Health Economics, CEMKA-EVAL, Bourg-la-Reine, France; 4Department of Endocrinology, Endokrinologikum, Center for Hormone and Metabolism, Ulm, Germany; 5Department of Endocrinology, Mario Negri Sud Foundation, Santa Maria Imbaro, Italy; 6Department of Family Medicine, University Miguel Hernández, Alicante, Spain; 7Department of Health Economics, EU-HEOR Novo Nordisk, Madrid, SpainAims: To compare the burden of disease (BoD) attributable to diabetes expressed in disability-adjusted life years (DALYs) for five European countries in 2010.Methods: DALYs lost to diabetes as the sum of years of life lost and years lived with disability were estimated by sex and age using country-specific epidemiological data and global disability weights. Data from various secondary sources were combined to estimate health loss due to diabetes for France, Germany, Italy, Spain, and the UK. National statistical databases were used and if necessary, community studies were used to derive the prevalence of diabetes by sex and age group, which were weighted proportionately for a national population burden of disease estimate. All identified data were adapted to the Global Burden of Disease methodology (2010) to calculate the burden attributable to diabetes. No age weighting and discounting was applied. Sensitivity to different sources of variation was examined. Germany and Italy lost the largest number of DALYs due to diabetes, with 5.9 and 5.8 per 1,000 inhabitants, respectively, followed by Spain (4.4), France (3.7), and the UK (2.9). The highest burden was caused by mortality due to diabetes, with the exception of the UK, for which the burden due to disability of diabetes was higher. Mean DALYs lost were higher for women in Germany, Italy, and Spain and shown to increase with age for all countries. Sensitivity analysis in variation in disability weights and uncertainty in epidemiological data were shown to have effects on DALYs lost. Conclusion: In spite of data limitations, the estimates reported here show that DALY loss due to diabetes imposes a substantial burden on countries. Cross-national variation in disease epidemiology was the largest source of variation in the burden of diabetes between countries.Keywords: prevalence, mortality, life expectancy, DALY